Intimate partner violence and incidence of common mental disorder - Marcela Franklin Salvador de Mendonça; Ana Bernarda Ludermir
ABSTRACT OBJECTIVE To investigate the association of intimate partner violence against women reported in the last 12 months and seven years with the incidence of common mental disorders. METHODS A prospective cohort study with 390 women from 18 to 49 years, registered in the Family Health Program of the city of Recife, State of Pernambuco; from July 2013 to December 2014. The Self Reporting Questionnaire-20 (SRQ-20) assessed mental health. Intimate partner violence consists of concrete acts of psychological, physical or sexual violence that the partner inflicts on the woman. Poisson regression was used to estimate crude and adjusted relative risks (RR) of the association between common mental disorders and intimate partner violence. RESULTS The incidence of common mental disorders was 44.6% among women who reported intimate partner violence in the last 12 months and 43.4% among those who reported in the past seven years. Mental disorders remained associated with psychological violence (RR = 3.0; 95%CI 1.9-4.7 and RR = 1.8; 95%CI 1.0-3.7 in the last 12 months, and seven years, respectively), even in the absence of physical or sexual violence. When psychological violence were related to physical or sexual violence, the risk of common mental disorders was even higher, both in the last 12 months (RR = 3.1; 95%CI 2.1-4.7) and in the last seven years (RR = 2.5; 95%CI 1.7-3.8). CONCLUSIONS Intimate partner violence is associated with the incidence of common mental disorders in women. The treatment of the consequences of IPV and support for women in seeking protection for themselves for public services is essential.